Effect of linear versus adaptive electronic continuing medical education regarding dental bleaching on dentists' knowledge and satisfaction - Mitra Zolfaghari; Aeen Mohammadi; Sedighe Sadat Hashemikamangar (Tabriz University of Medical Sciences, 2021)
Background: Studies on the efficacy of adaptive e-learning in dentistry are limited. This study aimed to compare the efficacy of linear and adaptive electronic continuing medical education (CME) courses about dental bleaching. Methods: This quasi-experimental study using a post-test control group design evaluated the efficacy of an electronic CME course on dental bleaching offered to 60 dentists who were non-randomly allocated in two linear and adaptive groups (n=30). One training session was held for participants of both the intervention and the control groups. At the end of the course, the learners participated in a post-test and completed a satisfaction questionnaire. SPSS 23 was used to analyze the results. An independent t test was used to assess the effect of type of intervention on the outcome of education, and Pearson's chi-square test was applied to assess the effect of the intervention on participants' satisfaction. Results: The mean post-test scores of participants were 6.33±1.47 for the linear group and 6.40±2.31 for the adaptive group. The mean satisfaction scores of participants were 4.02±0.53 for the linear group and 4.15±0.42 for the adaptive group. According to an independent t-test, the two groups were not significantly different in terms of post-test score (P=0.7) or level of satisfaction (P=0.2). Conclusion: The adaptive approach has considerable advantages and comparable efficacy to the linear method in terms of post-test score and self-reported knowledge and satisfaction of participants. Thus, this method of education may be as effective as the linear method for instruction in dental bleaching. The use of an adaptive approach is therefore recommended in educational curricula.